2019
DOI: 10.2478/johh-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

The seepage transport of heavy metal Pb2+ through sand column in the presence of silicon powders

Abstract: The coupled transport of heavy metals with suspended particles has been a topic of growing interest. The main purpose of this study is to experimentally investigate the seepage transport of heavy metal Pb2+ in the presence of silicon powders (SPs) through a sand column under different seepage velocities (v = 0.087–0.260 cm/s), injection Pb2+ concentrations (CP = 0–800 μg/ml) and SP sizes (D50 = 2.8–25.5 μm), which were likely to be encountered in practical engineering. The sand column was installed in a cylind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The topic of adequate modeling of the groundwater contamination by various substances, including heavy metals such as cadmium, mercury and lead has become one of the most important tasks for soil hydrologists in the last decade. The transport of solutes in soils, and its intensification due to the preferential flow (especially macropore flow), plays crucial role when problems related to the groundwater pollution are dealt with (Bai et al, 2019;Navrátil et al, 2015;Vogel et al, 2007).…”
Section: Hydrobiochemical Balance Of Thg In Forest Ecosystemmentioning
confidence: 99%
“…The topic of adequate modeling of the groundwater contamination by various substances, including heavy metals such as cadmium, mercury and lead has become one of the most important tasks for soil hydrologists in the last decade. The transport of solutes in soils, and its intensification due to the preferential flow (especially macropore flow), plays crucial role when problems related to the groundwater pollution are dealt with (Bai et al, 2019;Navrátil et al, 2015;Vogel et al, 2007).…”
Section: Hydrobiochemical Balance Of Thg In Forest Ecosystemmentioning
confidence: 99%
“…In fact, the factors affecting the coupled transport of suspended particles and heavy metal ions not only include the concentration of suspended particles, particle size [24,25], seepage velocity [26,27], temperature [28,29], gravity effect [30,31], and type and pH of heavy metal ions [32] but also include a variety of factors such as the type of porous media and physicochemical properties [33]. In this regard, many laboratory experiments have been accomplished to establish models for the deposition and release of suspended matters [34] as well as to establish the governing equations for the cotransport of multiple components [35][36][37]. Chrysikopoulos and Katzourakis [38] demonstrated that the dispersivity of colloids is not only a function of colloid size but also a function of seepage velocity by laboratory and field studies.…”
Section: Introductionmentioning
confidence: 99%